“History Must Be the Mirror of the Acts of the Great”: Stories from Plutarch in the Academic Art of the First Half of the 19th Century - Stepanova, Svetlana S. (Actual Problems of Theory and History of Art, 2022)
The antique themes of classicism are traditionally in the focus of art history. The purpose of this article is to clarify our understanding of this problematics in the historical and cultural context based on the analysis of a group of artworks. The thesis included in the title of the report, belongs to V. V. Popugaev. He was one of the members of the Free Society of Literature, Science and Art Lovers, the author of the work “’On Sublime in Fine Arts’. The connection of visual art with literature was considered a necessary quality that determined the aesthetic level of a work of art. The names of heroes of classical antiquity became symbols of heroism and civic virtues, and Plutarch’s ’Comparative biographies’ became the favorite reading of educated people. However, there are only few works based on plots from Plutarch in Russian historical painting. In The Death of Pelopidas painted by A. I. Ivanov, the traditional classical theme of the death of an ancient hero received a special interpretation; it is associated with the Christian theme of “mourning”. The artistic solution of Socrates in the battle of Potidea protects Alcibiades (GRM) by P. V. Basin testifies to the breadth of the Russian academic painter’s cultural outlook and romantic passion for ancient history. The plot of the painting Alcibiades and his friend escape by running out of their house, set on fire by enemies by Ya. F. Kapkov demonstrates the “heroic” aspect of male physicality, which in classicism was the basis of plastic ideas. The consideration of the artistic principles of classicism through the prism of reference to the plots from Plutarch allows us to analyze the range of individual creative solutions and the overall achievements of the academic school, which created a solid Foundation for the further development of Russian art.The study was carried out with the financial support of the Russian Foundation for Basic Research within the framework of the scientific project No. 19-012-00459.
Keywords: antiquity; classicism; academic art; historical painting; plot; creative interpretation; Plutarch; Comparative Biographies